STRES KERJA SEBAGAI MEDIASI: ORGANIZATIONAL CITEZENSHIP BEHAVIOR DAN QUALITY OF WORK LIFE, TURNOVER INTENTION - SIMEAO DA SILVA; ADYA HERMAWATI; ARIEF PURWANTO (BADAN PENERBITAN UNIVERSITAS WIDYAGAMA, 2021)
ABSTRACT This study aims to empirically describe Job Stress, Organizational Citizenship Behavior, Quality of Work Life, Turnover Intention to Nurses Guido Valadares National Hospital, Dili, Timor Leste. This research was an explanatory study that observed and explained the research variables in a cross-sectional manner. A quantitative approach was the main analytical method that is supported by a qualitative approach. The research population was 71 Nurses at the Guuido Valadares National Hospital, Dili, Timor Leste. All nurses were used as samples. Thus, this research was a type of census research and it was analyzed using Partial Least Square (PLS) with Software SmartPLS.The results indicated that the Organizational Citizenship Behavior and Quality of work Life had a significant effect on work stress and Turnover Intention directly. Besides, the results of the research that were tested indirectly showed that job stress was able to mediate the effect of Organizational Citizenship Behavior and Quality of work Life on Turnover Intention.Keyword: Work Stress, Organizational Citizenship Behavior, Quality of Work Life, Turnover Intention. ABSTRAK Penelitian ini bertujuan untuk menjelaskan secara empiris Stres Kerja, Organizational Citezenship Behavior, Quality of Work Life, Turnover Intention pada Perawat Rumah Sakit Nasional Guido Valadares Dili Timor leste. Penelitian ini merupakan penelitian eksplanatif yang menguji dan menjelaskan variabel - variabel penelitian secara Cross Sectional. pendekatan Kuantitatif sebagai metode analiis utama yang di dukung dengan pendekatan kualitatif. Populasi peneliitian adalah 71 orang Perawat Rumah sakit Nasional Guuido Valadares Dili Timor Leste. Keseluruhan perawat digunakan dijadikan sampel, dengan demikian penelitian ini merupakan jenis penelitian sensus dan di analisis menggunakan Partial Least Square (PLS) dengan Softwore SmartPLS.Hasil penelitian menunjukkan bahwa secara langsung Organizational Citezenship Behavior dan Qulity of work Life berpengaruh signifikan terhadap stres kerja dan Turnover Intention. Disamping itu, hasil peneltian yang diuji secara tidak langsung menunjukkan bahwa stress kerja mampu memediasi pengaruh Organizational Citezenship Behavior dan Qulity of work Life terhadap Turnover Intention.Kata Kunci: Stres Kerja, Organizational Citezenship Behavior, Quality of Work Life, Turnover Intention.